The unread critic. Higuchi Ichiyō’s diaries as bungei hyōron - Gala Maria Follaco (Bunron, 2020)
The diaries of Higuchi Ichiyō (1872–1896) are usually seen as examples of autobiographic writing, whereas her critical attitude is seldom considered. I argue that some parts of her nikki can be seen as criticism even if they do not resemble canonical forms of this kind of writing. As early as 1893, for instance, Ichiyō commented on shintai questioning the presumed ‘modernity’ of the most recent stylistic trends, and close reading of her notes reveals her deep knowledge of Japan's literature. These sections signal her literary consciousness at a very specific time: the years between 1893 and 1894, when, according to the dominant scholarship, her narrative production was still heavily dependent on previous models, thus not yet mature, a reading that my contribution will try to challenge. Further, her relationship with the contemporary bundan, as well as her acquaintance with Kagawa Kageki's thought will be considered, in order to assess her critical attitude against the backdrop of both her time and her literary education.